Difference Time Effect of Equilibration Before Freezing on The Quality of Spermatozoa Sapera Goats using Egg Yellow Tris - Prayogo, Danu; Susilowati, Suherni; Prastiya, Ragil Angga; Safitri, Erma; Agustono, Bodhi (Jurnal Medik Veteriner, 2022)
This study aimed to examine the effect of time differences on motility, viability, abnormality, and intact plasma membrane of spermatozoa of Sapera goats before freezing. This study used a Completely Randomized Design (CRD) with three settings, namely the equilibration time P1 (1 h), P2 (3 h), and P3 (4 h), each of six replications. The results of motility using One Way Anova statistical analysis through the Duncan Test were (P1) 71.50 ± 3.94, (P2) 66.00 ± 2.60, and (P3) 60.33 ± 2.42. The results of viability was (P1) 83.00 ± 6.16, (P2) 75.17 ± 4.70, and (P3) 69.00 ± 3.40. Abnormal results was (P1) 2.50 ± 0.55, (P2) 3.33 ± 1.18, and (P3) 6.50 ± 2.88. While the results of intact plasma membranes were (P1) 79.50 ± 8.50, (P2) 72.67 ± 5.28, and (P3) 65.67 ± 3.78. The conclusion of the study showed significant significant results (p<0,05) between the equilibration time and spermatozoa quality of Sapera goats before freezing. The highest presentation of motility, viability and overall plasma membrane was at an equilibration time of 1 h, while the lowest abnormality presentation was at equilibration time of 1 h.